Identification of chondroitin sulfate E proteoglycans and heparin proteoglycans in the secretory granules of human lung mast cells. - Stevens, R L (1988)
The predominant subclasses of mast cells in both the rat and the mouse can be distinguished from one another by their preferential synthesis of 35S-labeled proteoglycans that contain either heparin or oversulfated chondroitin sulfate glycosaminoglycans. Although [35S]heparin proteoglycans have been isolated from human lung mast cells of 40-70% purity and from a skin biopsy specimen of a patient with urticaria pigmentosa, no highly sulfated chondroitin sulfate proteoglycan has been isolated from any enriched or highly purified population of human mast cells. We here demonstrate that human lung mast cells of 96% purity incorporate [35S] sulfate into separate heparin and chondroitin sulfate proteoglycans in an approximately equal to 2:1 ratio. As assessed by HPLC of the chondroitinase ABC digests, the chondroitin [35S]sulfate proteoglycans isolated from these human lung mast cells contain the same unusual chondroitin sulfate E disaccharide that is present in proteoglycans produced by interleukin 3-dependent mucosal-like mouse mast cells. Both the chondroitin [35S]sulfate E proteoglycans and the [35S]heparin proteoglycans were exocytosed from the [35S]sulfate-labeled cells via perturbation of the IgE receptor, indicating that both types of 35S-labeled proteoglycans reside in the secretory granules of these human lung mast cells.